A survey-based, descriptive study of the occupational health experience of pregnant women doctors working in the public health sector in the Western Cape from 2009-2015 - Hiscock, Colleen J B (Department of Public Health and Family Medicine, 2017)
THE PURPOSE OF THE STUDY is to explore the experiences of pregnant women doctors working in public sector health facilities in the Western Cape and to ascertain whether occupational health laws and guidelines are being implemented for pregnant women doctors. This is being done in order to provide feedback to Western Cape department of health, so that if found necessary, recommendations for the improved occupational health of pregnant doctors can be implemented. THE OBJECTIVES are to conduct an internet-based survey of woman doctors who have experienced pregnancies while working in the public sector. The three main objectives are: 1. To describe the demographics of the respondents 2. To explore the experiences of the respondents with regard to working while pregnant 3. To assess the knowledge of occupational and other laws that relate to pregnant women at work. HYPOTHESIS: There is currently poor implementation of occupational health laws and services for pregnant doctors in the various government health facilities in the Western Cape SIGNIFICANCE OF THIS RESEARCH: "The progress of women in medicine is a long and continuing journey," AMA Women Physicians section (Anon.2013). The number of women graduating as doctors has increased. Many of these women form the mainstay of the public-sector workforce. Attention needs to be focused on ensuring the safety of pregnant women doctors and the safety of their unborn babies. METHODOLOGY OF STUDY: Study Design: This is a retrospective, survey-based, descriptive study using an electronic survey/ questionnaire as a tool. The survey includes both set answer options from which to choose as well as areas for respondents to give comments, which will add a qualitative element to the research. CHARACTERISTICS OF THE STUDY POPULATION: The study population consists of women doctors who took maternity leave while working in the state sector in the Western Cape from 2009-2015. INCLUSION AND EXCLUSION CRITERIA: Inclusion criteria: All women who complete and submit the survey will be included in the sample. No exclusion criteria are envisioned.